Long-term outcomes of the Atypical Hemolytic Uremic Syndrome after kidney transplantation treated with eculizumab as first choice - De Andrade, Luis Gustavo Modelli [UNESP]; Contti, Mariana Moraes [UNESP]; Nga, Hong Si [UNESP]; Bravin, Ariane Moyses [UNESP]; Takase, Henrique Mochida [UNESP]; Viero, Rosa Marlene [UNESP]; Da Silva, Trycia Nunes [UNESP]; Chagas, Kelem De Nardi; Palma, Lilian Monteiro Pereira (My University, 2017)
Introduction: The treatment of choice for Atypical Hemolytic Uremic Syndrome (aHUS) is the monoclonal antibody eculizumab. The objective of this study was to assess the efficacy and safety of eculizumab in a cohort of kidney transplant patients suffering from aHUS. Methods: Description of the prospective cohort of all the patients primarily treated with eculizumab after transplantation and divided into the therapeutic (onset of aHUS after transplantation) and prophylactic use (patients with previous diagnosis of aHUS undergoing kidney transplantation). Results: Seven cases were outlined: five of therapeutic use and two, prophylactic. From the five cases of therapeutic use, there was improvement of the thrombotic microangiopathy in the 48 hours following the start of the drug and no patient experienced relapse during an average follow-up of 21 months in the continuous use of eculizumab (minimum of 6 and maximum of 42 months). One patient died at 6 months, due to Aspergillus infection. From the two cases of prophylactic use, one patient experienced relapsed thrombotic microangiopathy after 4 months and another patient remained asymptomatic after 16 months of follow-up, both on chronic treatment. Discussion: The therapeutic use of eculizumab showed to be effective, with improvement of the microangiopathy parameters and persisting up to the end of the follow-up, without relapses. The additional risk of immunosuppression, leading to opportunistic infections, was well tolerated. The prophylactic use showed to be effective and safe; however, the doses and intervals should be individualized in order to avoid relapsed microangiopathy, especially in patients with factor H mutation.